Halophytes as new model plant species for salt tolerance strategies - Mann, Anita; Lata, Charu; Kumar, Naresh; Kumar, Ashwani; Kumar, Arvind; Sheoran, Parvender (Frontiers in Plant Science, 2023)
Soil salinity is becoming a growing issue nowadays, severely affecting the world’s most productive agricultural landscapes. With intersecting and competitive challenges of shrinking agricultural lands and increasing demand for food, there is an emerging need to build resilience for adaptation to anticipated climate change and land degradation. This necessitates the deep decoding of a gene pool of crop plant wild relatives which can be accomplished through salt-tolerant species, such as halophytes, in order to reveal the underlying regulatory mechanisms. Halophytes are generally defined as plants able to survive and complete their life cycle in highly saline environments of at least 200-500 mM of salt solution. The primary criterion for identifying salt-tolerant grasses (STGs) includes the presence of salt glands on the leaf surface and the Na+ exclusion mechanism since the interaction and replacement of Na+ and K+ greatly determines the survivability of STGs in saline environments. During the last decades or so, various salt-tolerant grasses/halophytes have been explored for the mining of salt-tolerant genes and testing their efficacy to improve the limit of salt tolerance in crop plants. Still, the utility of halophytes is limited due to the non-availability of any model halophytic plant system as well as the lack of complete genomic information. To date, although Arabidopsis (Arabidopsis thaliana) and salt cress (Thellungiella halophila) are being used as model plants in most salt tolerance studies, these plants are short-lived and can tolerate salinity for a shorter duration only. Thus, identifying the unique genes for salt tolerance pathways in halophytes and their introgression in a related cereal genome for better tolerance to salinity is the need of the hour. Modern technologies including RNA sequencing and genome-wide mapping along with advanced bioinformatics programs have advanced the decoding of the whole genetic information of plants and the development of probable algorithms to correlate stress tolerance limit and yield potential. Hence, this article has been compiled to explore the naturally occurring halophytes as potential model plant species for abiotic stress tolerance and to further breed crop plants to enhance salt tolerance through genomic and molecular tools.